Adaptive dosing approaches to the individualization of 13-cis-retinoic acid (isotretinoin) treatment for children with high-risk neuroblastoma - Veal, Gareth J. (2012)
PURPOSE: To investigate the feasibility of adaptive dosing and the impact of pharmacogenetic variation on 13-cisRA disposition in high-risk neuroblastoma patients. EXPERIMENTAL DESIGN: 13cisRA (160mg/m(2) or 5.33mg/kg/day) was administered to 103 patients ≤21 years and plasma concentrations of 13-cisRA and 4-oxo-13-cisRA quantitated on day 14 of treatment. 71 patients were recruited to a dose adjustment group, targeting a 13-cisRA C(max) of 2μM, with dose increases of 25-50% implemented for patients with C(max) values <2μM. A population pharmacokinetic model was applied and polymorphisms in relevant cytochrome P450 genes analyzed. RESULTS: 13-cisRA C(max) values ranged from 0.42–11.2μM, with 34/103 (33%) patients failing to achieve a C(max) >2μM. Dose increases carried out in 20 patients in the dose adjustment study group led to concentrations >2μM in 18 patients (90%). 8/11 (73%) patients <12kg, receiving a dose of 5.33mg/kg, failed to achieve a C(max) ≥2μM. Significantly lower C(max) values were observed for patients treated with 5.33mg/kg versus 160mg/m(2) (1.9±1.2 versus 3.1±2.0μM; mean±SD; P=0.023). C(max) was higher in patients who swallowed 13-cisRA capsules as compared to receiving the drug extracted from capsules (4.0±2.2 versus 2.6±1.8μM; P=0.0012). The target C(max) was achieved by 93% (25/27) versus 55% (42/76) of patients in these two groups respectively. No clear relationships were found between genetic variants and 13-cisRA pharmacokinetic parameters. CONCLUSIONS: Dosing regimen and method of administration have a marked influence on 13-cisRA plasma concentrations. Body weight-based dosing should not be implemented for children <12kg and pharmacological data support higher doses for children unable to swallow 13-cisRA capsules.